Postponement Of Elections Perspective Of Constitutional Law In The Indonesian Constitution - Alexander, Ongky; Okra, Rona (STAI Bumi Silampari, 2024)
Elections are a democratic party for the people as the holder of the highest sovereignty, namely electing members of the DPR, DPD, president, and vice president by the 1945 Constitution article 22E paragraph